Analysis of The Influence Of Firm Size, Liquidity, Leverage And Profitability On Firm Value Consumer Goods Industry On Stock Exchange Indoonesia (IDX) - Naca Perangin-angin; Ella Silvana Ginting (Junal Ilmu Manajemen, 2021)
This study aims to determine and analyze the effect of firm size, liquidity, leverage and profitability on firm value, either simultaneously or partially in consumer goods industry companies on the Indonesia Stock Exchange (IDX) in the period 2014 to 2017. The population in this study is industrial goods companies. consumption on the Indonesia Stock Exchange (IDX) during the 2014-2017 period, amounting to 45 companies. Sample selection using purposive sampling technique. The number of samples obtained as many as 25 companies. The data analysis method used is panel data regression analysis with the Eviews 8 application. Simultaneously, firm size, liquidity, leverage and profitability have a significant effect on firm value. Partially, firm size, leverage and profitability have a significant effect on firm value, while liquidity has no effect on firm value.